The effect of infection prevention and control programme for childcare workers in daycare centres: A systematic review - Pidjadee, Chakkrich; Soh, Kim Lam; Attharos, Tassanee; Soh, Kim Geok (W.B. Saunders, 2024)
Problem: Infectious diseases can easily spread in daycare centres (DCCs), primarily due to inadequate hygiene practices of both childcare workers and children. Therefore, childcare workers who provide direct care in early childhood play a crucial role in preventing and controlling infectious diseases in DCCs. This systematic review aims to identify current evidence and examine the effect of the infection prevention and control (IPC) programme for childcare workers in daycare centres, and to obtain a pooled estimate of the intervention's effect using meta-analysis, if possible Eligibility criteria: We searched literature through CINAHL, Medline, Cochrane Library, ScienceDirect, and Scopus databases, we also performed manual searches on Google Scholar and citation lists. Inclusion criteria comprised: 1) Experimental or quasi-experimental design studies that were published in the English language from October 1971 to December 2023, 2) Population focused on childcare workers responsible for early childhood in DCCs, 3) The intervention focused on the ICP programme, and 4) Outcomes related to childcare workers Sample: From 3,964 articles, eight studies were included in this review Results: Half of the total studies concentrated on hand hygiene intervention, while the remaining four addressed the prevention of infectious diseases and infection control. These studies reported an increase in knowledge, self-efficacy, and compliance regarding hand hygiene, and knowledge and practices related to infectious diseases. Two studies included nurses as conductors in the programme Conclusion: IPC programme effectively enhances some knowledge and performances in childcare workers Implication: Nurses can conduct IPC programme within daycare centres by utilizing evidence-based educational tools. Further research is needed to require well-reported studies, especially randomized controlled trials. Systematic review registration: PROSPERO CRD42023492592.